Intergovernmental organizations’ normative commitments to policy integration: the dominance of environmental goals - Tosun, Jale; Peters, B. Guy (Environmental science & policy, 2018)
Intergovernmental organizations (IGOs) influence policymaking in states by devising and promoting policy ideas. In this study, we examine to what extent a set of IGOs make normative commitments to integrate environmental concerns as well as to contrast this commitment to environmental policy integration (EPI) with climate policy integration (CPI) and energy policy integration (EnPI). Which characteristics of an IGO increase its likelihood to make a normative commitment to EPI? Do environment-related IGOs commit themselves to integrate environmental policy with concerns regarding climate change and/or energy? What is the ratio between the IGOs’ normative commitments to EPI relative to CPI and EnPI? Drawing on primary law texts of 78 IGOs, we find that organizations concentrating on Europe and IGOs in which the European Union (EU) Commission participates are more likely to commit themselves to EPI. Furthermore, the sectors covered by IGOs matter: organizations active in the field of general economic concerns and multi-issue IGOs are more likely than IGOs assigned to the ‘other’ category for embracing EPI. These findings still hold when controlling for the time when an IGO adopted its original or amended relevant primary law, its membership size and whether it is a United Nations organization. Environment-related IGOs commit themselves to a limited degree of CPI and EnPI. More broadly, the IGOs’ normative commitment to EPI clearly dominates over their commitment to EnPI and CPI.